ابن دريد وأعماله الأدبية: Ibn Durid and his Literary Works (Al-Qamar, 2021)
Ibn Durid was born in Basra in 223 Hijri. He got grammatical education and basic knowledge from Ibn-e-Akhi-Al-Isbae, Al-Sijstani and Al-Riyashi. He was one of the best scholars of literature, genealogy and lexicography. He was also the great poet of his time. He wrote many books and most of his books are mentioned in Al-Fahrist which is written by Ibn-e-Nadeem. His famous books are Al-Maqsurah, Al-Jamhrat-ul-Lugha, Kitab-ul-Ishtaqaq, Siffa-Tul-Sarj Wal-Lajam, Kitab-ul-Melahen and Kitab-ul-Mujtaba. He went to Oman from Basra and stayed there twelve years. During this period he gained knowledge of Arabic language and poetry. Then he went to Iran. There he met to the sons of Shah Mikal who were the governors of Persia. After this he wrote his book Jamahrat-ul-llugah and Al-Maqsurah in praised of shah Mekal’s sons. Ibn-e-Durid had a stroke at his last age, so he died in 321 Hijri.
Keywords: Ibn Durid; Al-Maqsurah; Jamahrat-ul-llugah; Kitab-ul-Ishtaqaq; Siffa-Tul-Sarj wal-Lajam; Kitab-ul-Melahan; Kitab-ul-Mujtaba